Ear drops for the removal of ear wax - Aaron, K; Cooper, T; Warner, L; Burton, M (John Wiley & Sons, Ltd, 2018)
Background Ear wax (cerumen) is a normal bodily secretion that can become a problem when it obstructs the ear canal. Symptoms attributed to wax (such as deafness and pain) are among the commonest reasons for patients to present to primary care with ear trouble. Wax is part of the ear's self-cleaning mechanism and is usually naturally expelled from the ear canal without causing problems. When this mechanism fails, wax is retained in the canal and may become impacted; interventions to encourage its removal may then be needed. Application of ear drops is one of these methods. Liquids used to remove and soften wax are of several kinds: oil-based compounds (e.g. olive or almond oil); water-based compounds (e.g. sodium bicarbonate or water itself); a combination of the above or non-water, non-oil-based solutions, such as carbamide peroxide (a hydrogen peroxide-urea compound) and glycerol. Objectives To assess the effects of ear drops (or sprays) to remove or aid the removal of ear wax in adults and children. Search methods We searched the Cochrane ENT Trials Register; Cochrane Register of Studies; PubMed; Ovid Embase; CINAHL; Web of Science; ClinicalTrials.gov; ICTRP and additional sources for published and unpublished trials. The date of the most recent search was 23 March 2018. Selection criteria Randomised controlled trials (RCTs) in which a 'cerumenolytic' was compared with no treatment, water or saline, an alternative liquid treatment (oil or almond oil) or another 'cerumenolytic' in adults or children with obstructing or impacted ear wax. Data collection and analysis We used the standard methodological procedures expected by Cochrane. The primary outcomes were 1) the proportion of patients (or ears) with complete clearance of ear wax and 2) adverse effects (discomfort, irritation or pain). Secondary outcomes were: extent of wax clearance; proportion of people (or ears) with relief of symptoms due to wax; proportion of people (or ears) requiring further intervention to remove wax; success of mechanical removal of residual wax following treatment; any other adverse effects recorded and cost. We used GRADE to assess the quality of the evidence for each outcome; this is indicated in italics. Main results We included 10 studies, with 623 participants (900 ears). Interventions included: oil-based treatments (triethanolamine polypeptide, almond oil, benzocaine, chlorobutanol), water-based treatments (docusate sodium, carbamide peroxide, phenazone, choline salicylate, urea peroxide, potassium carbonate), other active comparators (e.g. saline or water alone) and no treatment. Nine of the studies were more than 15 years old. The overall risk of bias across the 10 included studies was low or unclear. Primary outcome: proportion of patients (or ears) with complete clearance of ear wax Six studies (360 participants; 491 ears) contributed quantitative data and were included in our meta-analyses. Active treatment versus no treatment Only one study addressed this comparison. The proportion of ears with complete clearance of ear wax was higher in the active treatment group (22%) compared with the no treatment group (5%) after five days of treatment (risk ratio (RR) 4.09, 95% confidence interval (CI) 1.00 to 16.80); one study; 117 ears; NNTB = 8) (low-quality evidence). Active treatment versus water or saline We found no evidence of a difference in the proportion of patients (or ears) with complete clearance of ear wax when the active treatment group was compared to the water or saline group (RR 1.47, 95% CI 0.79 to 2.75; three studies; 213 participants; 257 ears) (low-quality evidence). Two studies applied drops for five days, but one study only applied the drops for 15 minutes. When we excluded this study in a sensitivity analysis it did not change the result. Water or saline versus no treatment This comparison was only addressed in the single study cited above (active versus no treatment) and there was no evidence of a difference in the proportion of ears with complete wax clearance when comparing water or saline with no treatment after five days of treatment (RR 4.00, 95% CI 0.91 to 17.62; one study; 76 ears) (low-quality evidence). Active treatment A versus active treatment B Several single studies evaluated 'head-to-head' comparisons between two active treatments. We found no evidence to show that one was superior to any other. Subgroup analysis of oil-based active treatments versus non-oil based active treatments We found no evidence of a difference in this outcome when oil-based treatments were compared with non-oil-based active treatments. Primary outcome: adverse effects: discomfort, irritation or pain Only seven studies planned to measure and did report this outcome. Only two (141 participants;176 ears) provided useable data. There was no evidence of a significant difference in the number of adverse effects between the types of ear drops in these two studies. We summarised the remaining five studies narratively. All events were mild and reported in fewer than 30 participants across the seven studies (low-quality evidence). Secondary outcomes Three studies reported 'other' adverse effects (how many studies planned to report these is unclear). The available information was limited and included occasional reports of dizziness, unpleasant smell, tinnitus and hearing loss. No significant differences between groups were reported. There were no emergencies or serious adverse effects reported in any of the 10 studies. There was very limited or no information available on our remaining secondary outcomes. Authors' conclusions Although a number of studies aimed to evaluate whether or not one type of cerumenolytic is more effective than another, there is no high-quality evidence to allow a firm conclusion to be drawn and the answer remains uncertain. A single study suggests that applying ear drops for five days may result in a greater likelihood of complete wax clearance than no treatment at all. However, we cannot conclude whether one type of active treatment is more effective than another and there was no evidence of a difference in efficacy between oil-based and water-based active treatments. There is no evidence to show that using saline or water alone is better or worse than commercially produced cerumenolytics. Equally, there is also no evidence to show that using saline or water alone is better than no treatment.